Geographical analysis of the automobile transport network of Zaporizhzhia region - Baiteriakov, Oleg; Kopylov, Denys (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2025)
Formulation of the problem. The need to study the pre-war state of the transport industry in the temporarily occupied territories is explained by the need to integrate it into the general transport network in the post-war period, considering the previous problems. The purpose of the article is to identify the state and spatial differences in the level of availability of the automobile transport network in the territory of Zaporizhzhia region on the eve of a full-scale russian invasion. Methods. The study used methods that allow obtaining a quantitative characteristic of the transport network coverage of the territory and comparing individual districts with each other. The indicators of road density by area, road density by population, weighted average road category index, and generalized Engel and Goltz coefficients have been calculated. Results. The analysis shows that the road networks of the administrative districts of Zaporizhzhia region as of 2021 were significantly differentiated in terms of the length of roads, their category, and density in relation to the area, according to the Engel coefficient. Even greater polarity was observed in the density of roads per population. At the same time, according to such generalized indicators as the weighted average category indicator of roads and the Goltz coefficient, the districts of the region are characterized by similarity, which indicates a fairly rational distribution of the territory by districts. A comparative analysis of the frames of motor transport networks was conducted; their impact on the temporal motor transport accessibility of the administrative districts of the region was identified using the calculated and constructed isochrone maps. The areas of the region have unique road transport network frameworks that affect the accessibility of the territory. In Zaporizhzhia and Melitopol regions, they have a radial configuration with the elements of a radial-ring configuration, in Polohy - a radial-nodal configuration, in Berdiansk - a radial configuration with the elements of cyclicity, and in Vasylivka - a cyclic configuration. Comparing the configuration of the territory of the districts and the corresponding settlement systems makes it possible to consider the frameworks of district road networks as close to the optimal. Considering the configuration of the region’s territory and the location of the city of Zaporizhzhia, the framework of the regional road network can be considered optimal; it provides a relatively uniform increase in time accessibility with distance from the regional center. However, the significant remoteness of the southern part of the region and, accordingly, its excessive temporal accessibility raise questions on the accelerated development of Melitopol and Berdiansk in the post-war period as subregional centers. Scientific novelty and practical significance. The state and spatial differences in the level of availability of the automobile transport network in the territory of Zaporizhzhia region and its administrative districts on the eve of full-scale russian aggression have been identified. The obtained data can be used for scientific substantiation of the development of the road transport network of Zaporizhzhia region and its administrative districts, considering the previous features and problems after the end of the full-scale russian aggression and de-occupation of this territory.